Socioeconomic differentials in premature mortality in Rome: changes from 1990 to 2001 - Ancona Carla; Forastiere Francesco; Agabiti Nera; Cesaroni Giulia; Perucci Carlo A (BMC, 2006)
Abstract Background While socioeconomic inequalities in mortality have widened in many countries, evidence of social differentials is scarce in Southern Europe. We studied temporal changes in premature mortality across socioeconomic groups in Rome between 1990 and 2001. Methods We analysed all 126,511 death certificates of residents of Rome aged 0-74 years registered between 1990-2001. A 4-level census block index based on the 1991 census was used as an indicator of socioeconomic position (SEP). Using routine mortality data, standardised mortality rates (per 100,000 inhabitants) were calculated by SEP and gender for four time periods. Rate ratios were used to compare mortality by gender and age. Results Overall premature mortality decreased in both genders and in all socioeconomic groups; the change was greater in the highest socio-economic group. In both men and women, inequalities in mortality strengthened during the 1990s and appeared to stabilise at the end of the 20th century. However, for 60-74 year old women the gap continued to widen. Conclusion Socioeconomic inequalities in health in Rome are still present at the beginning of the 21st century. Strategies to monitor the impact of SEP on mortality over time in different populations should be implemented to direct health policies.